Model of Enterpreneurship and Social-cultural and Market Orientation of Small Business Owners in Poland - Walczak-Duraj, Danuta (Comparative Economic Research. Central and Eastern Europe, 2011)
The subject of considerations of the text are the dominant socio-cultural and market orientations of small business in Poland. These orientations are related to the four dominant models of entrepreneurship in Poland: disaster, evolutionary, system and ethical, while their analysis is performed for Tyree basic perspectives. Firstly, from the perspective of the basic functions that can perform these orientations in the development or slowing of the enterprises market. Secondly, from the perspective of the dynamics of technological change and accompanying uncertainties in the sphere of business. Thirdly, the spatial perspective: local, regional and global scales. In the development of SMEs in Poland crucial meaning is legislation, steadily adapted to EU regulations, especially to the European Charter for Small Enterprises. Research conducted in Poland by many authors provide data for doing so, to confirm the hypothesis that among small businesses a vital role in shaping their work situation did not continue to play the market mechanisms and orientations, but mainly socio-cultural factors.